Advanced old age as a developmental dilemma: an in-depth comparison of established fourth age conceptualizations - Wahl, Hans-Werner; Ehni, Hans-Jörg (Journal of aging studies, 2020)
Distinguishing the Fourth Age (FoA) from the Third Age (ThA) has become a common practice in aging research. In this theoretical paper, we focus on four established conceptualizations of the ThA-FoA distinction, i.e., (1) Neugarten's work on the young-old vs. the old-old; (2) Laslett's concept of the innovative life period of the ThA; (3) Erikson's 9th life stage approach; and (4) Baltes' approach considering the FoA as the most radical incompleteness of the human condition. After a comparative descriptive analysis, we extract evaluative elements inherent in the four approaches according to six categories: (1) fundamental values; (2) positive evaluative elements; (3) negative evaluative elements; (4) the decline vs. growth view; (5) the continuity vs. discontinuity view; and (6) values related to practical issues. As an overarching result of our analysis, we conclude that all conceptions face - in different ways - dilemmas that seem difficult to solve. One option may be to give up all ambitions toward agency for the FoA and indeed qualify this phase as the “aging without agency” phase of life. Doing so, however, seems ethically questionable, because it would give up acknowledged values connected with a good human life such as human goal-directed autonomy and freedom. In conclusion, the ThA-FoA distinction, although arguably a needed and helpful roadmap for the recent decades of aging science, comes with enduring disadvantages and eventually even risks. Therefore, in future aging science, we recommend avoiding the ThA-FoA distinction or at least using it only in combination with a critical attitude.